Nutritional status of teenage female competitive figure skaters. - Ziegler, P.; Sharp, R.; Hughes, V.; Evans, W.; Khoo, C. S. (Journal of the American Dietetic Association, 2002)
OBJECTIVE: To assess the nutritional status of female competitive figure skaters during preseason, competitive season, and off-season. SUBJECTS: Eighteen female competitive figure skaters, age range 14 to 16 years, from the New England region. STATISTICS: Data was analyzed by repeated measures analysis of variance, Duncan Multiple Range Tests, one-sample t tests, and confidence intervals. DESIGN: Nutrient intakes were determined from 3-day diet records. Body composition was assessed through heights, weights, and underwater weighing. Blood samples were drawn for analysis of selected indexes of nutritional status. RESULTS: Height and weight did not differ significantly among the seasons. Body fat was 1.1 kg higher off-season compared with preseason. Energy intake over the 3 seasons did not vary significantly (mean preseason: 1,678 kcal/day; competitive season, 1,630 kcal/day; off-season: 1,673 kcal/day) (P>.05). During the competitive season 78%, 50%, and 44% of the skaters had intakes less than 67% of RDA for folate, iron, and calcium, respectively. Most of the biochemical indexes of nutritional status were within normal limits. CONCLUSIONS: The results indicate that teenage female skaters have relatively low energy intake and inadequate intakes of certain nutrients, which may account for some of the observed seasonal variations in blood markers of nutritional status. These findings point to the need for nutrition education for these athletes, especially during their competitive season when nutritional status may be compromised.